The Influence of Organizational Culture, Work Morale and Job Satisfaction Onemployee Altruism at the Padang City Population and Civil Registry Service - Puti Salsabila Arfi, Ashilah; Erianjoni, Erianjoni (Jurnal Locus Penelitian dan Pengabdian, 2025)
This research aims to identify the influence of organizational culture, work morale, and job satisfaction on altruism in Padang City Disdukcapil employees. This type of research is quantitative research using number calculations using statistical analysis. The method used in this research uses multiple linear regression. The population in this study were employees at the Padang City Civil Registration Population Service. The total sample in the research was 59 employees. The results of the research show that the Organizational Culture Variable has a significance value of 0.201 (>0.05) and t count -1.296 < t table 2.004, so it is concluded that the Organizational Culture Variable does not have a significant influence on the Altruism Variable. (H1 Rejected). The Work Morale variable has a significance value of 0.023 (<0.05) and t count 2.333 > t table 2.004, concluding that the Work Morale Variable has a Significant Influence on the Altruism Variable. (H2 Accepted). The Job Satisfaction variable has a significance value of 0.011 (<0.05) and t count 2.637 > t table 2.004, so it can be concluded that the Job Satisfaction Variable has a Significant Influence on the Altruism Variable. (H3 Accepted). It is known that the significance obtained is 0.000 (<0.05) and the calculated F value is 9.070 > F table 2.77, so we can conclude that the variables Organizational Culture, Work Morale and Job Satisfaction have a simultaneous (together) effect on the Altruism variable.